DISTRIBUTION OF Hoya multiflora Blume AT GUNUNG GEDE PANGRANGO NATIONAL PARK, INDONESIA - Rahayu, Sri; Kusmana, Cecep; Abdulhadi, Rochadi; Jusuf, Muhammad; Suharsono, Suharsono (Indonesian Journal of Forestry Research, 2010)
Hoya multiflora is one of the valuable germplasm in Indonesia that has been utilized as ornamental and medicinal plant. This epiphytic plant faces problems in decreasing habitat. As a means for developing a habitat framework for describing the distributions and ecological relations of H.multiflora at Gunung Gede Pangrango National Park, Bogor, Indonesia, ecological study of this species was established over the ranges of altitudes and characteristic vegetation structural types (primary and secondary forest, and plantation) present in the Park. Recognizing the fact that such study requires multidisciplinar y data, this paper explores the evidences from both herbarium sheets and field observations. The result of the study showed that the population of this species was only found at the Bodogol Research Station at elevation of 700 - 900 m above sea level (a.s.l.). Thus, the facts contradict with the evidence from the herbarium sheets of the Herbarium Bogoriense which have presumed that this species has a wide variation of altitudinal range from 20 to 1500 m a.s.l. (Indonesia) or 200 - 1400 m a.s.l. ( Java). The Bodogolâs population showed the clumped type of dispersion (Morisitaâs Index = 1.35), which indicated such environment that was characterized by patchy resources. Direction and speed of wind coupled with the topography are ecological factors that affect to the distribution of this parachute typed seeds of the H.multiflora.